Handbook of fiscal federalism - Ahmad, Ehtisham; Brosio, Giorgio (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
This book addresses fiscal relations between different levels of government under the general rubric of 'fiscal federalism', providing a review of the latest literature as well as an invaluable guide to practitioners and policy makers seeking informed policy options.
Includes bibliographical references and index.
gau 18/06/14
Loans
Keywords: Intergovernmental fiscal relations; Decentralization in government; Fiscal policy